Readiness Model of Pre-Service Science Teachers for Integrating Education for Sustainable Development (ESD) Based on Green Science: A Structural Equation Modeling Analysis - Suhendra Iskandar; Syadza Firdausiah (Journal of Natural Science and Integration, 2026)
The presence of Education for Sustainable Development (ESD) is crucial. Therefore, a comprehensive modeling approach is needed, particularly for pre-service teachers as future educators, a group that remains largely underexplored. This study aims to examine a structural model of the formation of the Intention to Integrate ESD among 199 pre-service science teachers at IAIN Sultan Amai Gorontalo. In this readiness model for ESD integration, sustainability literacy is positioned as the primary factor. At the same time, social norms and support, along with institutional support, are treated as contextual factors operating through psychosocial pathways. This study employed a quantitative approach, cross-sectional survey design to examine the structural relationships among variables. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results indicate that the proposed model explains a substantial proportion of variance in the intention to integrate ESD (R² = 0.744) and demonstrates adequate predictive relevance (Q² = 0.502). Institutional support emerges as the strongest predictor (β = 0.670, p = 0.000), while sustainability literacy shows a weaker yet significant effect (β = 0.279, p = 0.000). All constructs meet the required reliability and validity criteria. The findings reveal that, contrary to many theoretical assumptions emphasizing psychosocial mediation pathways, readiness to integrate ESD is predominantly influenced by institutional support rather than by sustainability literacy. In contrast, norms and social support exert their effects through indirect pathways, strengthened by sustainability literacy. This pattern further suggests the need for reformative institutional strategies in delivering ESD to students. Keywords: Education for sustainable development, psychosocial, sustainability literacy, SEM-PLS, SmartPLS 4